2012
DOI: 10.1039/c2pp25081k
|View full text |Cite
|
Sign up to set email alerts
|

Long-living structures of photochromic salicylaldehyde azine: polarity and viscosity effects from nanoseconds to hours

Abstract: In this study, we report on the effects of solvent viscosity and polarity on the photochromic salicylaldehyde azine (SAA) molecule by examining the steady-state and UV-visible absorption results in the time scale from nanoseconds to hours, in solution and in a polymer film. For the neutral structure, the viscosity strongly affects the lifetime of the photochromic (trans-keto) tautomer by suppressing the second order quenching process, and thus increasing the photochrome lifetimes in highly viscous solvents to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…22 Similarly as for SAA and other Schiff bases, the best fit for APA/HEX is obtained for the mixed first and second order kinetics model. 22,57,70 The fitted second order rate k 2 = 1.5 × 10 10 s −1 M −1 is similar to the averaged value found for SAA/HEX (1 × 10 10 s −1 M −1 ). 22,70 This process describes the intermolecular quenching process involving most probably two trans-keto tautomers and the proton exchange between them.…”
Section: Femto-to Microsecond Transient Absorptionsupporting
confidence: 82%
See 2 more Smart Citations
“…22 Similarly as for SAA and other Schiff bases, the best fit for APA/HEX is obtained for the mixed first and second order kinetics model. 22,57,70 The fitted second order rate k 2 = 1.5 × 10 10 s −1 M −1 is similar to the averaged value found for SAA/HEX (1 × 10 10 s −1 M −1 ). 22,70 This process describes the intermolecular quenching process involving most probably two trans-keto tautomers and the proton exchange between them.…”
Section: Femto-to Microsecond Transient Absorptionsupporting
confidence: 82%
“…22,57,70 The fitted second order rate k 2 = 1.5 × 10 10 s −1 M −1 is similar to the averaged value found for SAA/HEX (1 × 10 10 s −1 M −1 ). 22,70 This process describes the intermolecular quenching process involving most probably two trans-keto tautomers and the proton exchange between them. 22,24 On the contrary, there is a large difference between the fitted first order rate, which is k 1 = 1 × 10 5 s −1 for APA/HEX, ten times higher than that found previously for SAA/HEX (1 × 10 4 s −1 ).…”
Section: Femto-to Microsecond Transient Absorptionsupporting
confidence: 82%
See 1 more Smart Citation
“…of number of electrons per particle, the photo behaviour observed in transient absorption is probably more relevant than that found in TCSPC experiments. However, under photostationary conditions the concentration of the transient species is proportional to its lifetime [50], so the concentration of excited dyes per particle is several orders of magnitude smaller than concentration of electrons. Therefore, from the point of view of excited state selfquenching, the conditions of TCSPC experiments are more relevant to 1 Sun.…”
Section: Tablementioning
confidence: 99%
“…Ziółek et al reported that the lifetime of the trans-keto isomer of the anil-like compound salicylaldehyde azine can be increased from 65 to 500 μs by the use of more viscous solvents, and may even reach 700 μs if the compound is entrapped in a polyethylene film. 310 Viscosity is thought to inhibit thermal relaxation by providing friction to oppose the trans-cis isomerisation, whereas a polymer matrix is likely to restrict the space around the molecule such that more energy is needed to induce a conformational change. These effects are clearly of particular importance in gels, where -in contrast to bulk solids -interactions with solvent play a significant role.…”
Section: Intramolecular Proton Transfermentioning
confidence: 99%